2014
DOI: 10.1093/brain/awu343
|View full text |Cite
|
Sign up to set email alerts
|

Improving ideomotor limb apraxia by electrical stimulation of the left posterior parietal cortex

Abstract: Limb apraxia, a deficit of planning voluntary gestures, is most frequently caused by damage to the left hemisphere, where, according to an influential neurofunctional model, gestures are planned, before being executed through the motor cortex of the hemisphere contralateral to the acting hand. We used anodal transcranial direct current stimulation delivered to the left posterior parietal cortex (PPC), the right motor cortex (M1), and a sham stimulation condition, to modulate the ability of six left-brain-damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 50 publications
3
54
0
1
Order By: Relevance
“…These findings are in line with clinical studies, showing that cerebral lesions in middle frontal and parietal circuits can cause ideational apraxia (Hécaen, 1972;Bolognini et al, 2015;De Renzi and Lucchelli, 1988). Further investigations will be necessary to explore whether patients with movement disorders, such as patients with Parkinson's disease, would engage the same neural circuits during motor ideation.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…These findings are in line with clinical studies, showing that cerebral lesions in middle frontal and parietal circuits can cause ideational apraxia (Hécaen, 1972;Bolognini et al, 2015;De Renzi and Lucchelli, 1988). Further investigations will be necessary to explore whether patients with movement disorders, such as patients with Parkinson's disease, would engage the same neural circuits during motor ideation.…”
Section: Resultssupporting
confidence: 82%
“…In conclusion, ideational apraxia might not constitute a higherorder programming deficit of movement per se, but a combination of executive, language, and memory deficits or a diffuse reduction of cognitive resources (Gross and Grossman, 2008). Different lesion sites have been indicated as responsible for ideational apraxia, showing an involvement of mainly left temporo-parieto-occipital regions (Hécaen, 1972;Bolognini et al, 2015) even if patients with ideational apraxia have also been reported following frontal lesions, or basal ganglia damage (De Renzi e Lucchelli, 1988;Manuel et al, 2013;Huey et al, 2009). Patients with ideational apraxia can retain mental imagery abilities (Tomasino et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Before the experiment, each patient underwent a detailed interview about phantom sensations in order to assess: 1) the features of phantom limb sensations; 2) the features of PLP; 3) presence of voluntary or involuntary phantom movements, or immobilized phantom postures; 4) any other subjective descriptions of the qualities of the deafferentation pain. Patients were encouraged to describe exhaustively the quality of any subjective sensation they perceived in their phantom limb.…”
Section: Participantsmentioning
confidence: 99%
“…The choice of the stimulation parameters was based on previous positive effects obtained in PLP [3,4], but also considering the blinding issue of using a higher intensity (e.g., 2 mA) in a cross-over design [39]. Sham tDCS was applied with the same parameters and electrode montage of active tDCS, but the current lasted only for 30 sec [18].…”
Section: Tds Treatment Protocolmentioning
confidence: 99%
“…A right visual field advantage for the visual processing of tools (Garcea et al 2012) and a tool-selective response in the left IPL independent of visual field were reported , which is consistent with left hemisphere 10 dominance for tool-selective processing. Recent studies using anodal transcranial direct current stimulation (tDCS) showed that electrical stimulation of the left PPC improves the processing of gesture or imitation in healthy participants (Weiss et al 2013) and also in IMA patients (Bianchi et al 2015;Bolognini et al 2015), which further suggest the importance of left PPC for gesture processing. 15 Among the dorsal visual stream within the PPC, the dorso-dorsal pathway comprising the superior parietal lobule (SPL) and ventro-dorsal pathway, including the IPL, are distinct pathways (Rizzolatti and Matelli 2003;Binkofski and Buxbaum 2013).…”
Section: Introductionmentioning
confidence: 99%